Triple osteotomy for the correction of severe hallux valgus deformity: Patient reported outcomes and radiological evaluation. (August 2016) - Booth, Sean; Bhosale, Abhijit; Mustafa, Abubakar; Shenoy, Ravi; Pillai, Anand
Highlights: Triple osteotomy without lateral release is a contributing factor to early deformity recurrence. Patients need to be counseled on the risk of future metalwork removal and extended period of post operative swelling. Good radiological and patient reported outcomes are seen with double metatarsal and proximal phalanx osteotomies. Abstract: Background: Symptomatic Hallux valgus can be treated with metatarsal osteotomy combined with proximal phalangeal osteotomy, however this might not be sufficient to treat severe HV deformities. Methods: Fifteen feet in eleven female patients treated with double first metatarsal and proximal phalanx osteotomies without lateral release were prospectively studied and outcome measures including radiological angles and validated patient reported outcome scores collected. Results: Mean radiological follow up was 15 months and PROMs data 17 months. Mean hallux valgus and intermetatarsal angles were corrected from 45 to 24.7 ° and 18.7 to 7.4 ° respectively. There was an eight degree recurrence of hallux valgus angle. There was no wound problems, non-unions or evidence of avascular necrosis. The EQ-5D descriptive index showed a non-statistically significant improvement. All three elements of the MOxFQ score showed a statistically significant improvement: Forefoot pain (59–26.8), Walking and Stability (49.9–29.6) and Social Interaction (56.4–33.1) Conclusion: Triple osteotomy, without a lateral soft tissue release, leads to good radiological and functional outcomes in those with severe hallux valgus deformity. Patients need to be warned of the recovery time and potential for future metalwork removal. The risk of early recurrence suggests that a lateral release should be included in order to maintain a long lasting correction.